Pengaruh Kemampuan Kerja dan Kualitas Pelayanan terhadap Kepuasan Masyarakat pada Kantor Kecamatan Ciruas Kabupaten Serang - Nurhalifah Nurhalifah; Munawaroh Munawaroh (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
In a government agency or organization, it is one that requires serving the community well, community satisfaction is one of the factors to assess whether an agency or organization is good or not, work ability and service quality are the ones that can assess whether or not the community feels satisfied. This research aims to determine the effect of work ability and service quality on community satisfaction at the Ciruas District Office, Serang Regency. This research uses the literature review method, which is a research method used to collect, compile and synthesize existing research results. The research results in the study show that work ability influences community satisfaction, service quality influences community satisfaction, and work ability and service quality together influence community satisfaction.